Analisa Penerapan Sistem Merit Di Pemerintah Kota Mataram (Studi Pengisian Jabatan Pimpinan Tinggi Pratama Tahun 2022) - Hidayat, Rahmad (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2023)
One of the presidents prHiority programs is human resource development. Human resource development is one of the determining factors for organizational policies, including government organizations. In addition, human resources (apparatus) are also a whisper for the smooth running of bureaucratic reform. Human resources are one aspect of achieving the goals of government organizations, namely providing optimal public services. Therefore, it is necessary to apply the merit system to obtain human resources, in this case specifically the best State Civil Apparatus (ASN), including in the process of filling the pratama high leadership positions (JPT) within the Mataram City Government. This study aims to describe the application of the merit system in the government of Mataram City. This study uses a qualitative approach with data collection methods consisting of in-depth analysis, documentation and observation. Data analysis used technical qualitative data analysis. Data validity was tested using triangulation techniques. The research gave the result that the Mataram city government had basically implemented a merit system in ASN management. In filling out the JPT, it has been carried out with the stages of preparation, implementation and evaluation in accordance with the provisions. Many indicators of the criteria for implementing the merit system have also been created and implemented by the Mataram City government. Things that are still considered not responsive enough by directly inviting LANs who have experience in implementing merit systems. One of the deficiencies found in this study is related to an assessment center that is not yet owned by the Mataram city government.